Структура лексико-семантичного поля емотивних прикметників у сучасній англійській мові - Melnychuk, Natalia (Видавничий дім «Гельветика», 2021)
The article is devoted to the description of the structure of the lexico-semantic field of emotional adjectives in modern English. In modern linguistic research the concept of lexico-semantic field is relevant to the study of lexico-semantic structure of language as a complex of interconnected elements. In English linguistic picture of the world the semantic field of emotionality reflects a complex structure that encompasses elements of different parts of speech. Among them there is lexico-semantic field of emotional adjectives which represents the direct examples of verbal realization of human emotions within the linguistic picture of the world. It provides a continuity of connections of plural objects along with the possibility of describing these emotional units together without dividing the vocabulary (in contrast to the functional-semantic classes of emotional words, the study of which requires it). The semantic field contains an integral semantic feature that unites all its units and is expressed by a generalized meaning – an integral lexeme. It is a formal dominant word with a broad lexical meaning which combines a set of semantic features of the field, the most constant and relevant among which are sememes. In language, sememes are expressed lexically with the help of a certain number of lexemes or lexico-semantic variants of words, manifesting a significant denotative correlation with the semantic center of the field. In its turn, the semes determine the belonging of the word to a separate field structure, embodying their integral or differential nature. Thus, in the structure of the lexico-semantic field a word may have a complete, partial, potential or contextual correlation. The study of the lexico-semantic field of emotional adjectives is based on the principle of systematization and brings to the fore the connection of language with reality, its correlation with extraverbal reality. It is a rather complex structure in which the nucleus, perinuclear zone and periphery are separated.
The structure of lexico-semantic field of emotive adjectives in modern English
Keywords: семантична ознака; лексико-семантичне поле; емотивний прикметник; мовна картина світу; семантична структура; semantic feature; lexico-semantic field; emotional adjective; linguistic picture of the world; semantic structure